Left Ventricular and Atrial Functions in Hypertrophic Cardiomyopathy Patients with Very High LVOT Gradient: A Speckle Tracking Echocardiographic Study - ÇİNÇİN, AHMET ALTUĞ; ÖZBEN SADIÇ, BESTE; SARI, İBRAHİM; SÜNBÜL, MURAT; TİGEN, MUSTAFA KÜRŞAT (WILEY-BLACKWELL, 2014)
BackgroundDetermination of myocardial deformation (strain) by two-dimensional (2D) speckle tracking echocardiography (STE) is a new method for evaluating left ventricular (LV) regional function in patients with hypertrophic cardiomyopathy (HCM). The aim of this study was to assess LV and left atrial (LA) functions with 2DSTE in HCM patients and to investigate relation between strain analysis and LV outflow tract (LVOT) gradient. MethodsForty consecutive HCM patients (26 male, mean age: 47.715.2years), and 40 healthy volunteers (22 male, mean age: 46.611.2years) were included in the study. All subjects underwent a transthoracic echocardiography for evaluation of LV and LA functions with 2DSTE. The HCM patients were divided into 2 groups according to the presence of resting LVOT gradient >100mmHg. ResultsLeft ventricular global longitudinal strain (GLS), global radial strain (GRS), and global circumferential strain (GCS) were significantly lower in patients with HCM compared with controls (-20.3 +/- 3.6% vs. -24.1 +/- 3.4% P<0.001, 38.1 +/- 12.8% vs. 44.8 +/- 10.2% P=0.012, and -22.0 +/- 4.4% vs. -23.9 +/- 4.0% P=0.045, respectively). Although basal and apical rotation were similar between the groups, mid-rotation was significantly clockwise in HCM patients (-1.53 +/- 2.06 degrees vs. 0.05 +/- 1.7 degrees P<0.001). Both LA reservoir functions and LA conduit functions were significantly lower in HCM patients (21.6 +/- 9.1% vs. 39.4 +/- 10.6% P<0.001, and 10.5 +/- 4.3% vs. 15.7 +/- 5.3%, P<0.001). Fifteen patients had a resting LVOT gradient of >100mmHg and they had significantly decreased GLS, twist and untwist compared to the HCM patients with lower resting LVOT gradient (-18.7 +/- 2.3% vs. -21.2 +/- 3.9% P=0.016, 19.4 +/- 4.3 degrees vs. 23.5 +/- 7.4 degrees P=0.038 and -94.0 +/- 29.1 degrees/sec vs. -134.9 +/- 55.8 degrees/sec, 0.005, respectively). Although basal and apical rotation were similar between the 2 groups, mid-rotation was significantly clockwise in HCM patients with higher LVOT gradient (-2.52 +/- 1.76 degrees vs. -0.96 +/- 2.03 degrees, P=0.018). Correlation analysis revealed that LVOT peak velocity was associated with GLS (r=-0.358, P=0.023), LV mid-rotation (r=-0.366, P=0.024), and LV untwist (r=-0.401, P=0.013). ConclusionsLeft ventricular and LA functions are impaired in patients with HCM. 2DSTE is useful in determining patients with impaired myocardial mechanics. High LVOT gradient may be one of the responsible factors that trigger deterioration of LV longitudinal strain and twist mechanics in patients with HCM. Further studies are required to clarify the preliminary results of this study.
Keywords: hypertrophic cardiomyopathy; speckle tracking echocardiography; strain; twist; left ventricular; left atrial; 2-DIMENSIONAL STRAIN; MYOCARDIAL FIBROSIS; DYSFUNCTION; DYSSYNCHRONY; HEART